Integration of Bioinspired Fibrous Strands with 3D Spheroids for Environmental Hazard Monitoring. Issue 22 (5th May 2022) - Park, Chang Gyun; Jun, Indong; Lee, Sangmin; Ryu, Chang Seon; Lee, Sang‐Ah; Park, Jaeho; Han, Hyung‐Seop; Park, Honghyun; Manz, Andreas; Shin, Heungsoo; Kim, Young Jun
Abstract: Numerous methods have been introduced to produce 3D cell cultures that can reduce the need for animal experimentation. This study presents a unique 3D culture platform that features bioinspired strands of electrospun nanofibers (BSeNs) and aquatic cell lines to compensate for shortcomings in the current cell spheroid generation techniques. The use of BSeNs in 3D zebrafish liver cell cultures is found to improve liver and reproductive functions through spheroid‐based in vitro assays such as whole transcriptome sequencing and reproductive toxicity testing, with optimized properties exhibiting results similar to those obtained for fish embryo acute toxicity (FET, OECD TG 236) following exposure to environmental endocrine‐disrupting chemicals (17β‐Estradiol (E2), 4‐hydroxytamoxifen (4‐HT), and bisphenol compounds (bisphenol A (BPA) and 9, 9‐Bis(4‐hydroxyphenyl)fluorene (BPFL)). These findings indicate that the beneficial effects of bioinspired materials that closely mimic ECM environments can yield efficient zebrafish cells with intrinsic functions and xenobiotic metabolism similar to those of zebrafish embryos. As a closer analog for the in vivo conditions that are associated with exposure to potentially hazardous chemicals, the straightforward culture model introduced in this study shows promise as an alternative tool that can be used to further eco‐environmental assessment. Abstract : The beneficial effects of bioinspired strands of electrospun nanofibers (BSeNs) can compensate for shortcomings in the current cell spheroid generation techniques. Integrated 3D spheroids with BSeNs mitigate against the problems associated with hypoxia and the produced system is suitable for the testing of eco‐hazardous chemicals without the need for vertebrate platforms.